2013
DOI: 10.1007/s12155-013-9384-6
|View full text |Cite
|
Sign up to set email alerts
|

Process Modeling of Enzymatic Hydrolysis of Wet-Exploded Corn Stover

Abstract: The aim of this work was to investigate the optimal process conditions leading to high glucose yield (over 80 %) after wet explosion (WEx) pretreatment and enzymatic hydrolysis. The study focused on determining the "sweet spot" where the glucose yield obtained is optimized compared to the cost of the enzymes. WEx pretreatment was conducted at different temperatures, times, and oxygen concentrations to determine the best WEx pretreatment conditions for the most efficient enzymatic hydrolysis. Enzymatic hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…where A LA is the amount of levulinic acid obtained (mg/g DW of wood waste), A max LA is the maximum amount of levulinic acid obtainable (mg/g DW of wood waste) assuming that the maximum conversion of hexose to levulinic acid is 64.4% and the amount of hexoses from 1 g of cellulose is 1.111 g [15,51].…”
mentioning
confidence: 99%
“…where A LA is the amount of levulinic acid obtained (mg/g DW of wood waste), A max LA is the maximum amount of levulinic acid obtainable (mg/g DW of wood waste) assuming that the maximum conversion of hexose to levulinic acid is 64.4% and the amount of hexoses from 1 g of cellulose is 1.111 g [15,51].…”
mentioning
confidence: 99%
“…The variables were defined in five levels in the following ranges: 3.92-4.70 (R 0 ), 5-15% (TS), and 5-15% (EL). Levels of variables were determined according to preliminary tests and on the basis of literature reports (Cotana et al, 2015;Buratti et al, 2015;Rana et al, 2014;Pereira Ramos et al, 2015).…”
Section: Response Surface Methodology Design (Rsm)mentioning
confidence: 99%
“…In studies using corn stover, the highest cellulose hydrolysis yields were reported only at the highest enzyme concentration (40 mg protein per 1 g of glucan) and the highest biomass concentration (20% w/v). At lower enzyme concentrations, a signi cant decrease in hydrolysis yield was observed, even by 35% [33]. Also authors using rice straw as lignocellulosic raw material pointed out that obtaining the highest hydrolysis yield required precise optimization of process parameters.…”
Section: Optimization Of Enzymatic Hydrolysis Of Cellulose In Biomassmentioning
confidence: 99%
“…All analyzes were performed in triplicate. Based on glucose concentration, the yield of cellulose hydrolysis was determined as follows: 1where C Glu is the concentration of glucose (grams per liter) in the sample, C Cel is the cellulose content in biomass (per 1 gram of dry weight), C Biom is the initial biomass content (grams per liter)[33].Assessment of the suitability of microwave hydrotropic extraction in the production of ethanol from maize stillage biomassAlcoholic fermentation was carried out using stillage biomass after microwave hydrotropic extraction under the conditions selected in the rst stage of the study (pressure 117 PSI, extraction time 30 minutes, NaCS concentration 20% v/v, microwave generator power 300 W). The biomass after hydrotropic treatment was subjected to enzymatic hydrolysis using Cellic® CTec2 preparation under the conditions selected in the second stage of the study, ensuring the highest glucose concentration during a 24 h process, i.e.…”
mentioning
confidence: 99%